Students’ Perspective Towards the Effects of Anxiety in Technology-Based Assessment: A Qualitative Study - Putri, Nazmelia Indah; Basikin, Basikin (FKIP - Universitas Riau, 2025)
Test anxiety often appears in EFL students, especially in online assessments. The difficulties and anxiety associated with online testing must be taken into account when examining the impact of anxiety in technology-based assessments on EFL students. The purpose of this study is to explore the effects of anxiety in technology-based assessment on EFL students. This study also explores the students’ perspective on the connection between the uses of technology in assessment and anxiety. The researchers use qualitative research as the method of the research. This research was conducted at one of the universities in Yogyakarta. The interviews were conducted with four students from the second semester in-depth interview. In general, it is found that students tend to view online tests positively, perceiving them as a flexible and practical method of assessment. However, the findings also indicate that online test anxiety has a negative impact on the academic performance of EFL students and contributes to their perception of online assessments. It has been established that students experiencing high levels of anxiety may impair their reasoning and abstract thinking abilities, which can have a significant effect on the students’ academic performance.